A Field Experiment on the Impact of Incentives on Milk Choice in the Lunchroom. (January 2017) - List, John A.; Samek, Anya
Almost a third of US children ages two to nineteen are deemed overweight or obese, and part of the problem is the habitual decision to consume high-calorie, low-nutrient foods. We propose that the school lunchroom provides a "teachable moment" to engage children in making healthful choices. We conduct a field experiment with over 1, 500 participants in grades K to 8 from low-income households in the Chicago Heights, Illinois, School District and then evaluate the impact of small nonmonetary incentives on the selection of milk in the school lunchroom. At baseline, only 16 percent of children select white milk relative to 84 percent choosing chocolate milk. We find a significant effect of incentives, which increase white milk selection by 2.5 times, to 40 percent. One concern with incentives is that they may decrease intrinsic motivation to eat healthy, called "crowd-out of intrinsic motivation." However, we do not find evidence of "crowd-out"; rather, we see some suggestive evidence of the positive habit forming effect of incentives.